2009
DOI: 10.1016/j.aca.2009.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of multiple pure component 1H and 13C NMR spectra from two mixtures: Novel solution obtained by sparse component analysis-based blind decomposition

Abstract: Sparse Component Analysis (SCA) is demonstrated for blind extraction of three pure component spectra from only two measured mixed spectra in 13 C and 1 H nuclear magnetic resonance (NMR) spectroscopy. This appears to be the first time to report such results and that is the first novelty of the paper. Presented concept is general and directly applicable to experimental scenarios that possibly would require use of more than two mixtures. However, it is important to emphasize that number of required mixtures is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(39 citation statements)
references
References 38 publications
1
38
0
Order By: Relevance
“…Moreover, as stated by the authors, the BTEM approach is inapplicable when the number of experimentally measured spectra is less than the number of observed components. Here, as well as in recent publications, [16][17][18] we have demonstrated that the sparseness-based approach successfully estimates pure components when the number of available mixtures is less than the unknown number of components.…”
Section: Setting Up An Experimentssupporting
confidence: 78%
See 2 more Smart Citations
“…Moreover, as stated by the authors, the BTEM approach is inapplicable when the number of experimentally measured spectra is less than the number of observed components. Here, as well as in recent publications, [16][17][18] we have demonstrated that the sparseness-based approach successfully estimates pure components when the number of available mixtures is less than the unknown number of components.…”
Section: Setting Up An Experimentssupporting
confidence: 78%
“…18 The transform T is applied to X row-wise. If mixtures are recorded by higher-dimensional spectroscopic or spectrometric modality (2D NMR for example) a higher-dimensional transform T is applied to each mixture before it is mapped to its one-dimensional counterpart.…”
Section: Metabolic Profiling Of Biological Samples Involves Nuclear Mmentioning
confidence: 99%
See 1 more Smart Citation
“…have physical interpretation, factorization indeterminacies must be reduced to TT -1 =PΛ, whereas P is permutation matrix and Λ is diagonal matrix. These are standard indeterminacies in blind source separation and can be achieved if either sparseness, [5,[7][8][9], or statistical independence, [1,3,6], constraints are imposed on S. Sparseness constraints imply that at each pixel location (i 1 ,i 2 ) only few organs exists. In CT imaging, where pixel footprint is small, it is justified to assume that only one organ occupies each pixel footprint.…”
Section: X=asmentioning
confidence: 99%
“…The LMM-based representation has been successfully used recently for unsupervised segmentation of multi-spectral image, [3][4][5][6], as well as for blind extraction of analytes from mixtures spectra in NMR spectroscopy [7,8], mass spectrometry [7,9] and FT-IR spectroscopy [10]. In multi-spectral imaging A represents matrix of spectral profiles of the objects present in the image, while S represents matrix of spatial distributions of the same objects.…”
Section: X=asmentioning
confidence: 99%